Implementation the combined approach of path analysis and fuzzy DEMATEL for the analysis of BPM factors - Mehdi Ajalli; Amin Farhadi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The main goal of the current research is to analyze the factors of Business Process Management (BPM) in the stock exchange organization with the approach of factor analysis and fuzzy DEMATEL. For this purpose, first by reviewing the literature and interviewing experts, specialists and analysts of the Tehran Stock Exchange Organization, 10 key and critical factors in the success of the BPM system were identified and ten related hypotheses were proposed.Methodology: This research is applied in terms of purpose and descriptive-survey in terms of data collection method. The statistical population of this research regarding the examination and extraction of the final factors affecting the implementation of the BPM system, the opinions of all the employees of the brokerage companies under the supervision of the Tehran Stock Exchange Organization, is approximately 400 people. The sampling method is simple random and according to the Morgan table and the aforementioned formula, the sample size is 196 people. In this study, the designed questionnaire was provided to 250 managers, experts and specialists of the mentioned organization to express their views and opinions regarding the effectiveness of these factors. Also, the statistical population in relation to the evaluation and determination of the intensity of relationships between key factors and ultimately their importance and rank (in terms of the total intensity of effectiveness and influence) using the fuzzy DEMATEL technique is 80 managers and specialists with at least a bachelor's degree and 15 years of work experience in brokerage companies of the Tehran Stock Exchange Organization. Finally, a sample of 50 people from this population was used to evaluate the factors.Findings: The output of the factor analysis showed that ten factors are effective in implementing the system. Based on the output of the fuzzy DEMATEL, the organizational culture factor was ranked as the highest priority and reducing fear and anxiety in the organization was ranked as the lowest priority in terms of effectiveness of the BPM system.Originality/Value: In this study, the determining factors in the BPM of the organization have been identified and the influencing and influencing relationships between the factors have been explained for improving the organization's process.